2013
DOI: 10.1177/135945751302700103
|View full text |Cite
|
Sign up to set email alerts
|

Group Music Therapy on a Dementia Assessment Ward: An Approach to Evaluation

Abstract: This article presents an approach to evaluating a music therapy pilot project carried out on a dementia assessment ward, and introduces the framework for evaluation developed by the music therapist. This framework aims to describe and categorise patients' involvement in sessions, which may help to define clear outcomes for patients. It also highlights the relevance of music therapy treatment to the goals of the multi-disciplinary team on the ward, and to current thinking and policy about dementia care, as desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…These were originally created by Ruth Melhuish to evaluate dementia group work in a hospital setting (Melhuish, 2013) and have been further developed and tested by Mindsong, although they have not been formally validated. They are designed to be completed by the Music Therapists following each session in addition to clinical notes and aim to capture the client's levels of engagement, well-being and relationships with others during sessions (see Supplemental Appendix 2).…”
Section: Mindsong Scalesmentioning
confidence: 99%
“…These were originally created by Ruth Melhuish to evaluate dementia group work in a hospital setting (Melhuish, 2013) and have been further developed and tested by Mindsong, although they have not been formally validated. They are designed to be completed by the Music Therapists following each session in addition to clinical notes and aim to capture the client's levels of engagement, well-being and relationships with others during sessions (see Supplemental Appendix 2).…”
Section: Mindsong Scalesmentioning
confidence: 99%
“…Overall, full-text analysis of 23 articles was performed. Nine studies -two randomized controlled trials (RCT) [36,40]; one non-randomized trial (NRT) [39]; four Before and After studies (B&A) [37,[42][43][44] and two Case Series [38,45] -met the full inclusion criteria. Excluded full-text articles are listed in Table 2 and described in the Appendix.…”
Section: Study Selectionmentioning
confidence: 99%
“…The most frequent inclusion criteria entailed: old age; cognitive decline or acute confusion (defined in a variety of ways) and having the capacity to give consent and to participate in a Mbi. Five studies included only PwD [40,[42][43][44][45], but only in the study of Thornley et al was it clearly stated how diagnosis was made (ICD-10 criteria). The other 4 studies reported inclusion of PwD as well as patients with some degree of cognitive impairment (not formally quantified) [36,39] and/or delirium [37,38].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The assumption that humour, or a sense of humour as a personal characteristic, was not only a sign of wellbeing but also enabled healthy social interactions was widespread (Bright, 2010;Christenbury, 2017;Cobbett, 2016;Dennis & Rickson, 2014;Dwyer, 2007;Finch et al, 2016;Forsblom & Ala-Ruona, 2012;Frank, 2005;Hitchen et al, 2010;Melhuish, 2013;Mitchell, 2017;Pavlicevic, 2001;Potvin et al, 2018;Ridder & McDermott, 2014;Roberts, 2006;Rowland & Read, 2011). Lichtensztejn et al (2014) went as far as to document a client's responses to humour in music therapy to aid formal assessments of cognitive capacity and Geretsegger et al (2015) also identified humour as being important in ascertaining the level of participation when working with a child in music therapy.…”
Section: A Sense Of Humourmentioning
confidence: 99%
“…In several articles, humour was directly linked with playfulness and fun and is referred to in musicking (Small, 1994) with people across the lifespan (Aasgard, 2000;Jones, 2012;Loombe, 2017;Margetts et al, 2013;Melhuish, 2013;Oldfield & Bunce, 2001;Trondalen, 2001). Some of these authors also explored how humour could be used to share control, to playfully challenge (Guerrero, 2014), and address issues of dominance in sessions.…”
Section: Humour and Playfulnessmentioning
confidence: 99%